Ultrasound Stimulation Increases Neurite Regeneration in Injured Dorsal Root Ganglion Neurons through Mammalian Target of Rapamycin Activation - Han, Sungmin; Park, Jinyoung; Choi, Won Seok; Youn, Inchan (MDPI, 2020)
Ultrasound stimulation (US) is reported to be a safe and useful technology for improving injured nerve regeneration. However, the intracellular mechanisms underlying its stimulatory effects are only partially understood. Mammalian target of rapamycin (mTOR) signaling is involved in neuronal survival and axonal outgrowth. In this study, we investigated the effect of US on regeneration of injured dorsal root ganglion (DRG) neurons and activation of the mTOR pathway. We showed that US significantly increased neurite regeneration and enhanced mTOR activation. Moreover, the expression of growth-associated protein-43 (GAP-43), a crucial factor for axonal outgrowth and regeneration in neurons, was significantly increased by US. These data suggest that US-induced neurite regeneration is mediated by upregulation of mTOR activity, which promotes the regeneration of injured DRG neurons.
Keywords: PERIPHERAL-NERVE REGENERATION; LOW-INTENSITY-ULTRASOUND; GLYCOLIC ACID) CONDUITS; SCIATIC-NERVE; OUTGROWTH; NEUROMODULATION; PTEN/MTOR; LASER